Clinical case of accomodative paresis while taking psychotropic drugs - D. S. Afanasyeva (Российский офтальмологический журнал)
There is a tendency for the prevalence of mental disorders to increase among people of different age. A patient taking psychotropic and other medications can see a doctor of any profile. This article presents a clinical case where treatment received in connection with a psychoemotional disorder led to the development of an undesirable reaction from the accommodative apparatus of the eyes, which led the patient to an ophthalmologist. In the presented case, a young patient suffered from sharply decreased near vision, while taking antipsychotics, antidepressants and anticholinergics with antiparkinsonian action. Based on the complaints, anamnesis and the results of an ophthalmological examination, a diagnosis was made: paresis of accommodation of both eyes; complex hypermetropic astigmatism. The development of accommodation disturbance was considered as a side effect of taking the central anticholinergic blocker biperiden, so it was recommended to consult with her psychiatrist about adjusting the therapy. At the follow-up visit a month later, the patient noted complete restoration of near vision. The restoration of accommodation can be explained by the cessation of the anticholinergic effect due to the abolition of biperiden. The described case shows the relevance of a thorough history taking, including a history of treatment of concomitant diseases and disorders, in patients of any age.